A blinded, randomized, placebo‐controlled trial of the safety of lokivetmab (ZTS‐00103289), a caninized anti‐canine IL‐31 monoclonal antibody in client‐owned dogs with atopic dermatitis. Issue 6 (19th September 2016) - Michels, Gina M.; Walsh, Kelly F.; Kryda, Kristina A.; Mahabir, Sean P.; Walters, Rodney R.; Hoevers, Jacquelien D.; Martinon, Olivier M.
Abstract : Background: Lokivetmab (ZTS‐00103289) is a caninized anti‐canine IL‐31 monoclonal antibody that has demonstrated efficacy in reducing pruritus associated with atopic dermatitis (AD) in dogs in field trials. Hypothesis/Objectives: This study evaluated the safety of lokivetmab in a randomized, double blind, placebo‐controlled trial in client owned dogs with AD with minimal restrictions on concomitant medications and co‐morbidities. Animals: Clinicians at 14 veterinary clinics enrolled client owned dogs ( n = 245) with chronic AD. Methods: Dogs were randomized at a 2:1 ratio to receive either lokivetmab (1.0–3.3 mg/kg) or placebo administered subcutaneously on days 0 and 28. Clinicians examined dogs, and collected blood and urine for assessment of clinical pathology and immunogenicity (days 0, 28 and 42). Results: There were no immediate hypersensitivity reactions (e.g. wheals, vomiting). Discomfort at administration occurred in 5.1% of dogs and was similar in frequency and severity between lokivetmab‐ and placebo‐treated groups. Pruritus was reported as an adverse event during the study less frequently in the lokivetmab‐treated group (4.9% and 19.3%, respectively); otherwise, adverse events occurred at a similar frequency between treatment groups. There were no clinically important differences between groups in clinical pathology results. Treatment‐induced immunogenicity was found in 2.5% of lokivetmab treated dogs. A wide variety of concomitant medications were used with no clinically apparent adverse interactions. Conclusions and clinical importance: Among a diverse population of 162 client owned dogs with a clinical diagnosis of AD, treatment with two monthly doses of lokivetmab was safe, based on observed adverse events and clinical pathology results over a 42 day period. Abstract : Background – Lokivetmab (ZTS‐00103289) is a caninized anti‐canine IL‐31 monoclonal antibody that has demonstrated efficacy in reducing pruritus associated with atopic dermatitis (AD) in dogs in field trials.Hypothesis/Objectives – This study evaluated the safety of lokivetmab in a randomized, double blind, placebo‐controlled trial in client owned dogs with AD with minimal restrictions on concomitant medications and co‐morbidities.Conclusions and clinical importance – Among a diverse population of 162 client owned dogs with a clinical diagnosis of AD, treatment with two monthly doses of lokivetmab was safe, based on observed adverse events and clinical pathology results over a 42 day period.